Subcellular Biochemistry
DOI: 10.1007/0-387-27600-9_7
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Mechanism of myo-Inositol-1-Phosphate Synthase

Abstract: Abstract:The first and rate-limiting step in the biosynthesis of myo-inositol is the conversion of D-glucose 6-phosphate to 1L-myo-inositol 1-phosphate catalyzed by 1L-myo-inositol 1-phosphate synthase (MIP synthase). MIP synthase has been identified in a wide variety of organisms from bacteria to humans and is relatively well-conserved throughout evolution. It is probably homotetrameric in most if not all cases and always requires NAD ϩ as a cofactor, with NADH being reconverted to NAD ϩ in the catalytic cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 50 publications
1
53
0
Order By: Relevance
“…Phosphorylation of Ser-374 may perturb access of the substrate to the catalytic domain or may destabilize the induced fit by creating steric hindrance, thus decreasing catalytic activity. Additionally, the catalytic domain is populated with hydrophobic residues (15,17). The negative charge of the phosphate group may alter the electrostatic balance of these residues and thus cause further perturbation of enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of Ser-374 may perturb access of the substrate to the catalytic domain or may destabilize the induced fit by creating steric hindrance, thus decreasing catalytic activity. Additionally, the catalytic domain is populated with hydrophobic residues (15,17). The negative charge of the phosphate group may alter the electrostatic balance of these residues and thus cause further perturbation of enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of yeast MIPS shows that it is a homotetramer ( Fig. 1B) (15,16), whereas mammalian MIPS exists as a trimer (10). Each monomer has three major domains: a catalytic domain that binds the substrate glucose 6-phosphate, an NAD ϩ -binding domain, and a central domain, consisting of the N and C termini, which stabilizes the two other domains (17).…”
mentioning
confidence: 99%
“…Ins biosynthesis involves two enzymes: (1) D(L)- myo -inositol-3(1)-phosphate synthase (MIPS, EC 5.5.1.4) catalyzes the conversion of glucose 6-phosphate to myo -D(L)-inositol-3(1)-phosphate [20], and (2) inositol monophosphatase (IMPase, EC 3.1.3.25), which dephosphorylates inositol phosphate to yield Ins [21]. Both enzymes have been thoroughly characterized in a number of organisms and several high-resolution 3D protein structures from multiple species have been experimentally determined for these proteins (S1 Table in Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…The MIB pathway utilizes two enzymes, myo-inositol phosphate synthase (MIPS) and inositol monophosphatase (IMPA), to generate myo-inositol endogenously from glucose-6-phosphate (G-6-P) in a two-step reaction (Geiger and Jin, 2006). The study by Fiol et al (Fiol et al, 2006b) was the first to identify upregulation of MIPS mRNA in response to acute hyperosmotic challenge in tilapia gill, and since then, several studies have confirmed induction of the MIB pathway in other euryhaline species exposed to salinity challenge (Evans and Somero, 2008;Kalujnaia et al, 2009;Kalujnaia et al, 2010;Kalujnaia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%